(untitled) (Ameghiniana, 2013)
In the present paper all specimens of Lepidopteris from different localitis in’ the Argentine Triassic are revised. Some specimens have been found with cuticle and they may be refered to the well known species Lepidopteris stormbergensis (Seward), Townrow. Some specimens which were described by Frenguelli as Caüipteridium argentinum are also referecl to the sarne species of Lepidopteris. Another fragmentary material from Santa Clara in Mendoza is described as Lepidopteris sp, It is concluded that Lepidopteris stormbergensis is present only in Triassic Formations in Argentina: Cacheuta and Potrerillos Forrnations from Mendoza Province and El Tranquilo Formations in Santa Cruz Province.